Influence of coach and parental support towards career decision-making self-efficacy among Malaysian national student athletes - Retnam, Elaiyaraj (2018)
The purpose of this study is to examine influence of coach and parental support towards career decision-making self-efficacy among Malaysian national student athletes. This is a descriptive and correlational research study and based on theoretical framework of Social Cognitive Career Theory. This study focused on the national athletes who are currently studying Pre-University in the National Sports Schools. By using random sampling technique, 145 student athletes from 2 National Sports School, namely, Bukit Jalil Sports School (BJSS) and Tunku Mahkota Ismail Sports School (TMISS) participated in the study. This study is a quantitative research developed by using three established instruments to test on two independent variables which are parental support with Career-Related Parent Support Scale and coach influence adopted from Career-Related Parent Support Scale alongside with one dependent variable which is career decision making self-efficacy using Career Decision Making Self Efficacy Scale – Short Form. 30 respondents were involved in pilot test to ensure the reliability of the instruments. The data were then analyzed by using descriptive and correlative statistics. This study provided evidences of career decision making self-efficacy of National student athletes. The analysis showed that athletes demonstrated a moderate level on coach influence and career decision making self-efficacy while parental support is found to be high. Besides that, results from the correlation analysis indicate that the two predictors, which is parental support and coach influence, have significant positive relationship with career decision making self-efficacy at 0.05 level of significant. The test for regression analysis indicates, among the two predictors, parental support was the dominant predictor in student athletes career decision making self-efficacy with (beta = 0.573) followed by coach influence (beta= 0.218). This finding may be taken into considerations useful to the Human Resource Department as it may be useful for the national student athletes in the career development progress and for key stake holders in developing new policies or system to support the national student athletes. By emphasizing on the career development of national student athletes, athletes could easily boost their confidence and knowledge about career needs and have a secured future upon retiring as an athlete. This finding also provides opportunity to add new perspective to career development theory. The implications of the findings were further discussed in the last chapter.